Sustainability of Agroecosystems 2018
DOI: 10.5772/intechopen.72966
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Variety of Soil Microorganisms Depending on the Diversity of the Soil Tillage System

Abstract: Soil is an ecosystem capable of producing the resources necessary for the development of the living organisms. Soil microorganisms (bacteria and fungi) are responsible for biomass decomposition, biogenic element circulation, which makes nutrients available to plants, biodegradation of impurities, and maintenance of soil structure. The presence of microorganisms in soil depends on their chemical composition, moisture, pH, and structure. Human activity has an indispensable influence on the formation of ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 72 publications
1
18
0
2
Order By: Relevance
“…Finally, the correlation between bacterial richness in 2011 and bacterial richness in 2016 indicated that the evolution of soil bacterial communities was dependent on their previous state [ 89 ]. This suggests that bacterial communities may respond differently according to the historical farming and land use management [ 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the correlation between bacterial richness in 2011 and bacterial richness in 2016 indicated that the evolution of soil bacterial communities was dependent on their previous state [ 89 ]. This suggests that bacterial communities may respond differently according to the historical farming and land use management [ 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical and physical attributes are involved in soil microorganisms development (Borowik & Wyszkowska, 2016; Furtak & Gajda, 2018; Wang et al., 2017). Data enable observe that microorganisms’ activity was more affected positively by soil chemical, than physical attributes, and therefore basal respiration and nodulation were higher in the subsoiled soil that presented improvements in chemical structure.…”
Section: Discussionmentioning
confidence: 99%
“…Both the intensification and limitation of the cultivation method may significantly alter the proportions of individual groups of soil microorganisms and relationships between various members of these groups. The degradation of the soil environment resulting from intensive agriculture practices increases the risk of biodiversity loss [53]. According to Jaskulska et al [54], the number of soil bacteria and fungi after changing the conventional tillage system with simplified cultivation increased by 17.3% and 45.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%